Art and abstract objects - Mag Uidhir, Christy (Oxford : Oxford University Press, 2013)
'Art and Abstract Objects' presents a lively philosophical exchange between the philosophy of art and core areas of philosophy. A team of contributors examine the ontological nature of repeatable artworks - such as plays, novels, and films - as abstract objects, which are immaterial, causally inert, and outside space-time.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Art and philosophy; Abstraction